How does contemporary selection shape oak phenotypes?. (14th August 2020) - Alexandre, Hermine; Truffaut, Laura; Klein, Etienne; Ducousso, Alexis; Chancerel, Emilie; Lesur, Isabelle; Dencausse, Benjamin; Louvet, Jean‐Marc; Nepveu, Gérard; Torres‐Ruiz, José M.; Lagane, Frédéric; Musch, Brigitte; et al.
Abstract: Most existing forests are subjected to natural and human‐mediated selection pressures, which have increased due to climate change and the increasing needs of human societies for wood, fibre and fuel resources. It remains largely unknown how these pressures trigger evolutionary changes. We address this issue here for temperate European oaks ( Quercus petraea and Q. robur ), which grow in mixed stands, under even‐aged management regimes. We screened numerous functional traits for univariate selection gradients and for expected and observed genetic changes over two successive generations. In both species, growth, leaf morphology and physiology, and defence‐related traits displayed significant selection gradients and predicted shifts, whereas phenology, water metabolism, structure and resilience‐related traits did not. However, the direction of the selection response and the potential for adaptive evolution differed between the two species. Quercus petraea had a much larger phenotypic and genetic variance of fitness than Q. robur . This difference raises concerns about the adaptive response of Q. robur to contemporary selection pressures. Our investigations suggest that Q. robur will probably decline steadily, particularly in mixed stands with Q. petraea, consistent with the contrasting demographic dynamics of the two species.